If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 5) + 4(x + 4) = 0 Reorder the terms: 6(5 + x) + 4(x + 4) = 0 (5 * 6 + x * 6) + 4(x + 4) = 0 (30 + 6x) + 4(x + 4) = 0 Reorder the terms: 30 + 6x + 4(4 + x) = 0 30 + 6x + (4 * 4 + x * 4) = 0 30 + 6x + (16 + 4x) = 0 Reorder the terms: 30 + 16 + 6x + 4x = 0 Combine like terms: 30 + 16 = 46 46 + 6x + 4x = 0 Combine like terms: 6x + 4x = 10x 46 + 10x = 0 Solving 46 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-46' to each side of the equation. 46 + -46 + 10x = 0 + -46 Combine like terms: 46 + -46 = 0 0 + 10x = 0 + -46 10x = 0 + -46 Combine like terms: 0 + -46 = -46 10x = -46 Divide each side by '10'. x = -4.6 Simplifying x = -4.6
| 2n-60=5n | | 3(x-4)=1-1(2x-7) | | 9n-15=3(2n-1) | | 2(x+12)=13 | | 450-296.55=x | | -4a=-36 | | -4a=-39 | | 6y=-18 | | t+-9=5 | | x+-7=-4 | | n-(-2)=8 | | y-6=-18 | | aR+bR=124a | | Ra+Rb=ab | | R*a+R*b=a*b | | R*A=3 | | R=1e+R | | 0.6x+0.5=0.15 | | -0.3y-0.6=0.9 | | 2n+8= | | 10=6-2x | | 26.5=1+0.25x | | 26.5=1-0.25x | | 23-2y=15 | | -112-2y=-24 | | 9x-(6x-1)=2 | | 2t+7=1 | | 3b-6=21 | | -2*7= | | 2(c+4)=4c-10 | | 8y-2=4y+22 | | x=-9 |